Basmalah dalam Pandangan Ulama Al-Quran - Zali Rahman (At-Tahfidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2021)
This research departs from the differences of opinion between previous and current scholars regarding the position of the Basmalah recitation, especially the basmalah at the beginning of the al-Fatihah. Some of them said basmalah should not be read while reading surah al-Fatihah because the Prophet did not read it, some said it was obligatory to read it because there was a hadith from the Prophet which explained that the Prophet read Basmalah when he read al-Fatihah. As seen above, each opinion adheres to the history attributed to the Prophet, both the narration is a speech or an act of the Prophet. Departing from the existence of these contradictory hadiths, the author tries to explain the contradiction by using the analysis of Hadith Mukhtalif Science, and using data from scholars of the ulum al-Quran.